Healing trauma in group settings : the art of co-leader attunement - Wise, Stephanie (New York, NY : Routledge, 2020)
"Healing Trauma in Group Settings offers a unique focus on the highly valuable role of attuned co-leader relationships in the practice of healing trauma. Drawing on their extensive experience of co-leadership, the editors demonstrate how to maximize the potential for effective trauma work while remaining attuned to the needs of individual group members and the group as a whole"--
OCLC-licensed vendor bibliographic record.
Keywords: Post-traumatic stress disorder -- Treatment; Multiple psychotherapy; PSYCHOLOGY / Psychopathology / Post-Traumatic Stress Disorder (PTSD); PSYCHOLOGY / Mental Health; PSYCHOLOGY / Psychotherapy / Group